Ketidaksesuaian Penyampaian Harga Tanah: Tanggung Jawab Pejabat Pembuat Akta Tanah - Afifah, Salwah Nur; Saleng, Abrar; Nur, Sri Susyanti (Universitas Widya Gama Malang, 2023)
This study aims to analyze the PPAT's responsibility for the land sale and purchase deed he made in the event that the parties do not convey the actual land price and analyze the validity and consequences that will arise if the land sale and purchase deed does not include the actual land price. This research is normative research, where in this research the subject matter of the study is in the form of the application of normative law in action to any particular legal event that occurs in society. The results of the study show that if the PPAT knows that the price entered by the parties is included in the sale and purchase agreement, the PPAT must refuse to make the sale and purchase deed. In addition, it is mandatory for PPAT as an extension of the government to play an active role in providing counseling or guidance to prospective buyers and sellers not to reduce the actual price of the land sale and purchase price between them. Then regarding the validity and consequences that will arise in the future if the land sale and purchase deed does not include the actual price of the land and without the PPAT knowing as the maker, it can result in the land sale and purchase deed (authentic deed) degrading its evidentiary power to a private deed because it has been made with ways that deviate or are not in accordance with procedures both materially and formally. And it is possible that in the future it will be discovered that the price stated in the land sale and purchase deed is incorrect, so there is a possibility that the parties (seller and buyer) may be entangled in Article 266 paragraph (1) of the Criminal Code.